2018
DOI: 10.1177/1098300718762744
|View full text |Cite
|
Sign up to set email alerts
|

Improving Student Behavior in Art Classrooms: An Exploratory Study of CW-FIT Tier 1

Abstract: Disruptive student behavior is a concern for educators (Everston & Weinstein, 2006), commonly recognized as a reason many teachers leave the profession (McKinney, Campbell-WhatelyKea, 2005). Research has demonstrated that 2% to 16% of students exhibit behavior that does not meet teacher expectations, negatively affecting their own and their classmates' education (Hester, 2003). A study of behavioral expectations showed that teachers considered students' self-control and cooperation the most important factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
4
12
0
Order By: Relevance
“…Results of the study indicated that middle school art teachers were able to implement the intervention with levels of fidelity consistent with fidelity found in other CW-FIT studies (Caldarella, Williams, Hansen, & Wills, 2015; Nelson et al, 2018; Wills, Iwaszuk, Kamps, & Shumate, 2014). The fidelity for most items ranged from 96.67% to 100%.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Results of the study indicated that middle school art teachers were able to implement the intervention with levels of fidelity consistent with fidelity found in other CW-FIT studies (Caldarella, Williams, Hansen, & Wills, 2015; Nelson et al, 2018; Wills, Iwaszuk, Kamps, & Shumate, 2014). The fidelity for most items ranged from 96.67% to 100%.…”
Section: Discussionsupporting
confidence: 78%
“…The timers had both a beeping and a vibrating function, but teachers felt the students would display desired behavior only when they heard the audible beep to get points. For this reason, they switched the function to vibrate, as has sometimes been done in past studies of CW-FIT (see, for example, Nelson et al, 2018). Teachers awarded points after every 5 min when they felt the timer vibrates.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations